The Influence of Project-Based Learning Model on Students' Learning Outcomes in Reaction Rate Material - Hanisa, Siti; Mustapa, Kasmudin; Ratman, Ratman; Ahmar, Dewi Satria; Mawaddah, Hayyatun (Journal of Disruptive Learning Innovation (JODLI), 2023)
This study aims to determine the effect of the Project Based Learning learning model on student learning outcomes in the matter of reaction rates at SMA Negeri 1 Ampibabo. The population in this study were all students of class XI IPA at SMA Negeri 1 Ampibabo, academic year 2022/2023, totaling 150 people consisting of 5 classes. This type of research is a type of quasi-experimental research with a research design using the pretest and posttest of the experimental group and the control group. Sampling was carried out based on special considerations (purposive sampling) with a research sample of XI IPA E totaling 30 students as an experimental class using the Project Based Learning learning model, XI IPA A totaling 30 students as a control class using conventional learning models. Data collection techniques using test techniques, Based on the results of the study it can be concluded that there is an influence of the learning model on the material on the reaction rate on student learning outcomes at SMA Negeri 1 Ampibabo. This is based on the results of calculations using the SPSS Version 26 application where the value of Sig (2-tailed) = 0.007 <0.05 then Ha is accepted and Ho is rejected, meaning that there is a significant influence between the use of the Project Based Learning learning model on the reaction rate material on learning outcomes students at SMA Negeri 1 Ampibabo.